Rabies in a Captive Lowland Tapir (Tapirus terrestris) - Pereira, Fernanda M.A. M.; Oliveira, Ayisa R de; Soares-Neto, Lauro L.; Munhoz, Laura; Fernandes, Laura S.; Santos, Daniel O dos; Carvalho, Thaynara P de; Langoni, Helio [UNESP]; Santos, Renato L. (Elsevier, 2022)
Rabies is a severe viral zoonosis of mammals and causes irreversible neurological damage. We describe the clinical presentation and anatomopathological lesions of rabies in a captive lowland tapir (Tapirus terrestris) in Bauru, São Paulo State, Brazil. The clinical course of the disease lasted 6 days and was characterized by progressive neurological deterioration and death. The main anatomopathological findings were non-suppurative encephalitis and presence of Negri bodies within neurons. Direct immunofluorescence and mouse inoculation tests were positive for rabies virus. This is the first report of rabies in a lowland tapir and highlights the importance of disease prevention under managed care and continuous control measures in urbanized environments.
Keywords: Negri bodies; pathology; rabies; tapiridae; wildlife; zoonosis